EFL Students’ Perception of Listening Skills in Core English and IELTS Subjects: A Study at a State University in Battambang - Doeurn Channyalin; Soll Sievmei; Ny Monyneath; Ly Sovann; Choeurn Chanratana (UNIB Press, 2024)
Listening skills are one of the most important and hard skills for non-native students which contains many sub-skills. Therefore, students require more practice with sufficient support materials to master their competence. There are two subjects providing listening skills practice for students in their program. However, the study on the view of students on these subjects has not been found in the research context. A This research aims to explore EFL students’ perception of listening skills embedded in IELTs and Core English courses, and the comparison of these two courses. This study used a quantitative research method with a survey design focused on the students in year 3 and year 4 of an English major. The researchers used types of listening, such as selective listening, intensive listening, comprehension listening, critical listening, interactive listening, and discriminative listening, as the main questions for conducting the questionnaires. As a result of the research, researchers compared the total between Core English and IETLS subjects and found that studying Core English and IELTS subjects can help students improve their listening skills but the most improvement is the IETLS subject. Furthermore, future researchers could employ this research to identify further listening difficulties or to compare the results. They can also use it as a reference to their study.